SPRTN protease and checkpoint kinase 1 cross-activation loop safeguards DNA replication - Halder, Swagata; Torrecilla, Ignacio; Burkhalter, Martin D.; Popović, Marta; Fielden, John; Vaz, Bruno; Oehler, Judith; Pilger, Domenic; Lessel, Davor; Wiseman, Katherine; Singh, Abhay Narayan; Vendrell, Iolanda; et al. (Nature communications, 2019)
The SPRTN metalloprotease is essential for DNA-protein crosslink (DPC) repair and DNA replication in vertebrate cells. Cells deficient in SPRTN protease exhibit DPC-induced replication stress and genome instability, manifesting as premature ageing and liver cancer. Here, we provide a body of evidence suggesting that SPRTN activates the ATR-CHK1 phosphorylation signalling cascade during physiological DNA replication by proteolysis-dependent eviction of CHK1 from replicative chromatin. During this process, SPRTN proteolyses the C-terminal/inhibitory part of CHK1, liberating N-terminal CHK1 kinase active fragments. Simultaneously, CHK1 full length and its N-terminal fragments phosphorylate SPRTN at the C-terminal regulatory domain, which stimulates SPRTN recruitment to chromatin to promote unperturbed DNA replication fork progression and DPC repair. Our data suggest that a SPRTN-CHK1 cross-activation loop plays a part in DNA replication and protection from DNA replication stress. Finally, our results with purified components of this pathway further support the proposed model of a SPRTN-CHK1 cross-activation loop. Cells deficient in SPRTN protease activity exhibit severe DNA-protein crosslink induced replication stress and genome instability. Here the author reveal a functional link between the SPRTN protease and the CHK1 kinase during physiological DNA replication.